Abdominal tuberculosis manifested as tuberculosis of the urachal sinus in an adolescent and the role of laparoscopy in the management: A rare case report - Sze, Li Siow; Hon, Leong Sha; Chee, Ming Wong (BioMed Central Ltd., 2016)
Background: Abdominal tuberculosis (TB) is an uncommon affliction in adolescence. It is usually associated with pulmonary tuberculosis. The disease is caused by lymphohaematogenous spread after primary infection in the lung or ingestion of infected sputum and has a typically protean and nonspecific presentation. The occurrence of TB in an urachal remnant is probably from the contiguous spread of an abdominal focus or mesenteric lymph node. Urachal TB is a rare entity, with only two reported cases in the literature. We report here a case of clinically silent pulmonary and abdominal TB that manifested in the infection of an urachal sinus and highlight the role of laparoscopy in its diagnosis and treatment. Case presentation: A 14-year-old boy presented to our institution with peri-umbilical swelling and purulent discharge from his umbilicus for 2 weeks duration. There were no radiological, microbiological or clinical evidences of TB in the initial presentation, though he had close social contact with someone who had TB. A computed tomography scan of the abdomen confirmed the diagnosis of an urachal abscess. An incision and drainage procedure was performed followed by a course of antibiotics. A scheduled laparoscopic approach later showed that the peritoneum and serosal surface of the small and large intestines were studded with nodules of variable sizes, in addition to the urachal sinus. The histology of the resected tissues (urachal sinus and nodules) was consistent of TB infection. He recovered fully after completing 6 months of anti-tuberculous therapy. Conclusion: This report highlights a rare case of TB urachal abscess in an adolescent boy, the difficulties in the diagnosis of abdominal tuberculosis, the need to consider TB as a cause of urachal infection in endemic areas and the use of laparoscopy in both diagnosis and treatment